DTI and MTR Measures of Nerve Fiber Integrity in Pediatric Patients With Ankle Injury - Holmes, Scott A.; Karapanagou, Anastasia; Staffa, Steven J.; Zurakowski, David; Borra, Ronald; Simons, Laura E.; Sieberg, Christine; Lebel, Alyssa; Borsook, David (Frontiers in Pediatrics, 2021)
Acute peripheral nerve injury can lead to chronic neuropathic pain. Having a standardized, non-invasive method to evaluate pathological changes in a nerve following nerve injury would help with diagnostic and therapeutic assessments or interventions. The accurate evaluation of nerve fiber integrity after injury may provide insight into the extent of pathology and a patient's level of self-reported pain. The aim of this investigation was to evaluate the extent to which peripheral nerve integrity could be evaluated in an acute ankle injury cohort and how markers of nerve fiber integrity correlate with self-reported pain levels in afferent nerves. We recruited 39 pediatric participants with clinically defined neuropathic pain within 3 months of an ankle injury and 16 healthy controls. Participants underwent peripheral nerve MRI using diffusion tensor (DTI) and magnetization transfer imaging (MTI) of their injured and non-injured ankles. The imaging window was focused on the branching point of the sciatic nerve into the tibial and fibular division. Each participant completed the Pain Detection Questionnaire (PDQ). Findings demonstrated group differences in DTI and MTI in the sciatic, tibial and fibular nerve in the injured ankle relative to healthy control and contralateral non-injured nerve fibers. Only AD and RD from the injured fibular nerve correlated with PDQ scores which coincides with the inversion-dominant nature of this particular ankle injuruy cohort. Exploratory analyses highlight the potential remodeling stages of nerve injury from neuropathic pain. Future research should emphasize sub-acute time frames of injury to capture post-injury inflammation and nerve fiber recovery.